Potts Shunt in a Child With End-Stage Pulmonary Hypertension After Late Repair of Ventricular Septal Defect. (July 2013) - Petersen, Cecilie; Helvind, Morten; Jensen, Tim; Andersen, Henrik Ørbæk
We report on a 10-year-old boy with medically refractory pulmonary arterial hypertension (PAH) and end-stage right heart failure after closure of a ventricular septal defect. The boy was a candidate for lung transplantation (LTX), but an alternative option was to create an Eisenmenger physiology with right-to-left shunting. The shunt could be created either as an intracardiac or as an extracardiac shunt. We decided to create a Potts shunt, a direct anastomosis between the left pulmonary artery and the descending aorta. The Potts shunt functioned as a right-to-left shunt, thus reducing the afterload on the right ventricle. The boy's clinical condition improved markedly, so he was discharged two weeks after the procedure. The ultimate therapeutic option for medically refractory PAH is LTX or heart–lung transplantation, but because of the short life span after LTX, time was bought by postponing the time of transplantation.